A Comprehensive Overview of Research Methods on the Influence of Lactic Acid, Body Composition, Swimming Velocity, and Heart Rate on 100-Meter Freestyle Swimming Performance - Navjeet Singh Bhullar; Dr. Pravin Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study provides a comprehensive overview of research methods used to investigate the influence of lactic acid, body composition, swimming velocity, and heart rate on the performance of 100-meter freestyle swimmers. The objective is to systematically explore how these physiological and biomechanical factors interact and contribute to performance outcomes in short-distance freestyle swimming. By reviewing various methodologies, including physiological testing, body composition analysis, velocity measurements, and heart rate monitoring, the study aims to identify key patterns and correlations that can enhance understanding and improve training strategies for swimmers. The overview covers experimental designs, data collection techniques, and analytical approaches, offering insights into best practices and potential challenges in this area of research. This comprehensive analysis serves as a valuable resource for researchers and practitioners seeking to optimize performance through evidence-based methods.